Unattended Radar Station Design for Dewline Application. Executive Summary. - Gersten,E J; Abriel,W E; Bell,S E; Golden,J R; Gorham,J T (1978)
The Executive Summary is a very short synopsis of the 'Unattended Radar Station Design Application' study to investigate the Feasibility of utilizing a string of Unattended Radars in the Arctic. The study is conceptual relative to design, installation, operation, maintenance and support of Unattended Stations and attendant problems such as security, reliability, maintainability, availability and life cycle cost. Cost drivers and problems are identified, and potential solution alternatives with recommendations presented. The conclusion is that with reasonable development, economical Unattended Arctic Radar Stations are possible. (Author) See also Volume 2, AD-A059 510.